Population dynamics of Parrotfish (Scarus rivulatus) in Seribu Islands Waters - Nurfajar Nurfajar; Mennofatria Boer; Nurlisa A Butet (Depik, 2024)
Parrotfish capture fisheries production in the Seribu Islands Waters is quite high. This study aims to determine several aspects related to parrotfish (S. rivulatus) population dynamics in the Seribu Islands Waters. This research was conducted for 12 months, starting from January to December 2022. The results of the analysis of the growth coefficient of male parrotfish are K=0.54 year-1, while females' growth coefficient is K=0.75 year-1. Growth parameters from the von Bertalanffy equation, for males Lt=312.4[1-exp-0.54(t-(-0.158))] and females Lt=280.4[1-exp-0.75(t-(0.12))]. Recruitment occurred twice during the 2022 period, with peak recruitment of males occurring in April and August and females in May and September. Completion mortality (F) was higher than natural mortality (M). Male parrotfish F=1.06M=0.63 and females F=4M=0.80. Mean first-capture size (Lc) for male fish Lc=174 mm and females 147 mm.Keywords:Over-exploitationParrotfishSeribu Islands